Is the Elapsed Time following the Placement of a Ventriculoperitoneal Shunt Catheter an Individual Risk Factor for Shunt Fractures? - Kaplan, Metin; Cakin, Hakan; Ozdemir, Niyazi; Gocmez, Cuneyt; Ozturk, Sait; Erol, Fatih S. (Karger, 2012)
In this study, we examined whether the resistance of peritoneal catheters against the retraction force changed over time following shunt placement, and the role of this resistance in shunt fracture is discussed. We investigated peritoneal catheters removed from patients treated with a ventriculoperitoneal shunt because of hydrocephalus; previously, patients underwent shunt revision. The maximum tension, maximum elongation and elongation percentages of the peritoneal catheters were measured. The mean and maximum tension values of the revised peritoneal catheters were increased compared to the unused catheters. The maximum elongation and elongation rates were significantly decreased. The changes in the maximum elongation, elongation rate and tension values were unrelated to the time elapsed after catheter insertion. This finding indicates that the time elapsed following peritoneal catheter placement was not an individual factor based on the strength of the response of the organism to the foreign body and the mechanical trauma exposed in shunt fractures. Copyright (C) 2013 S. Karger AG, Basel
Keywords: Catheter; Cerebrospinal fluid shunt; Hydrocephalus; Shunt complications